HUBUNGAN TINGKAT PENGETAHUAN TENTANG GIZI IKAN DENGAN PEMANFAATAN MAKAN IKAN SEBAGAI NUTRISI BAGI IBU HAMIL DALAM PENCEGAHAN STUNTING - Yuanita Novi Riani; Agnes Isti Harjanti; Danny Putri Sulistyaningrum (Pusat Riset dan Inovasi Nasional, 2023)
Nutrition for pregnant women should receive attention because nutrition influences fetal development. However, in the reality, the knowledge of pregnant women about nutrition for the fetus is still low. One of the efforts to prevent the fetal growth problem is by consuming fish. This research determined the correlation between knowledge level about fish nutrition and the importance of consuming fish as the nutrition for pregnant women to prevent stunting. This correlation analytical research design used a retrospective approach. The population consisted of 82 respondents from all first and second-trimester mothers at MIP Mustofiah, Weding Bonang Village, Demak. The sample consisted of 76 participants taken with purposive sampling. The applied instrument was questionnaires of knowledge level and food frequency. The data analysis applied Pearson's product-moment correlation test. The results showed that the pregnant women at MIP Mustofiah, Weding village, did not consume fish as an important nutrient for pregnant women in preventing stunting. They did not consume fish because they had lower knowledge about the nutrition of fish. The evidence was the obtained p-value, 0.000 lower than 0.05. The value indicated the correlation between the knowledge level about fish nutrition and the consumption of fish as the nutritional source for pregnant women in preventing stunting. The observable correlation was strong, indicated by r-value = 0.803. The results recommended pregnant women improve their knowledge by following health socialization, reading mass media, and improving the consumption of fish as a nutritional source of pregnant women. These actions will improve the efforts to prevent stunting. Keywords: Knowledge, Fish Consumption, Pregnant Women